2018
DOI: 10.1097/md.0000000000011394
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical activity and risk of prevalent psoriasis

Abstract: Psoriasis is a common chronic relapsing immune-mediated inflammatory disease, whose prevalence has increased in recent years. Some physicians believe that physical activity is associated with numerous health-related benefits in adults with dermatoses. While numerous studies have suggested an association between psoriasis and physical activity, others have yielded contradictory results. The aim of our study was to evaluate the association between the level of physical activity and prevalence of psoriasis.A comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
1
21
1
Order By: Relevance
“…Gisondi et al ( 18 ) reported that SUA levels were significantly higher in obese patients than in non-obese patients with psoriasis. Zheng et al ( 45 ) highlighted the fact that intense physical activity lowered the prevalence of psoriasis by reducing fat accumulation. Our meta-analysis showed that SUA levels were significantly higher in patients with moderate to severe psoriasis in European and American regions and Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Gisondi et al ( 18 ) reported that SUA levels were significantly higher in obese patients than in non-obese patients with psoriasis. Zheng et al ( 45 ) highlighted the fact that intense physical activity lowered the prevalence of psoriasis by reducing fat accumulation. Our meta-analysis showed that SUA levels were significantly higher in patients with moderate to severe psoriasis in European and American regions and Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published meta-analysis combined data of 13 studies including a total of 149,499 participants [ 46 ]. There was no significant difference in the level of exercise between people without and with psoriasis when analyzed for the overall effect but the subgroup analysis showed that patients with psoriasis performed vigorous exercises significantly less than controls (RR 0.76; 95% CI 0.67–0.85; p < 0.00001).…”
Section: Association Between Psoriasis and Cardiovascular Risk Factormentioning
confidence: 99%
“…Furthermore, the severity of psoriasis is significantly correlated with comorbidities [40,41]. Although psoriasis is not an immediately life-threatening disease, it still reduces the quality of life of patients and brings a heavy economic burden on society [42]. Additionally, some patients with psoriasis, especially women, will have quite serious psychological disorders that will [43,44].…”
Section: Discussionmentioning
confidence: 99%